Augmented Internal Fixation of Distal Femoral Fractures: Current Concepts, Biomechanical Rationale, Indications, and Clinical Evidence—A Review - Hristo Hristov; Yordan Andonov (THE JOURNAL OF THE BULGARIAN ORTHOPAEDICS AND TRAUMA ASSOCIATION, 2026)
Distal femoral fractures remain difficult to treat, particularly in older patients with poor bone quality and in highly comminuted injuries with loss of medial cortical support. Objective: To review the biomechanical rationale, indications, techniques, and reported outcomes of augmented internal fixation. Methods: A focused review of English-language clinical studies, biomechanical investigations, systematic reviews, and meta-analyses was undertaken. PubMed/MEDLINE and ScienceDirect were searched using terms related to distal femoral fractures and augmentation; reference lists were screened for additional relevant publications. Results: The literature identifies poor bone quality, medial comminution or bone loss, and suboptimal construct configuration as major contributors to fixation failure. Reported augmentation strategies include polymethyl methacrylate cement, supplementary medial plating, nail–plate constructs, and structural allografts. These methods may improve construct stability and support earlier rehabilitation in selected high-risk fractures, although the evidence is heterogeneous and largely based on biomechanical studies and clinical case series. Conclusion: Augmentation should be individualized according to host biology, fracture morphology, bone stock, and fixation stability. Comparative clinical evidence remains limited.